Cancer stem cells: A review from origin to therapeutic implications - Atashzar, Mohammad Reza; Baharlou, Rasoul; Karami, Jafar; Abdollahi, Hamid; Rezaei, Ramazan; Pourramezan, Fatemeh; Zoljalali Moghaddam, Seyed Hamid (Journal of cellular physiology, 2020)
Cancer stem cells (CSCs), also known as tumor‐initiating cells (TICs), are elucidated as cells that can perpetuate themselves via autorestoration. These cells are highly resistant to current therapeutic approaches and are the main reason for cancer recurrence. Radiotherapy has made a lot of contributions to cancer treatment. However, despite continuous achievements, therapy resistance and tumor recurrence are still prevalent in most patients. This resistance might be partly related to the existence of CSCs. In the present study, recent advances in the investigation of different biological properties of CSCs, such as their origin, markers, characteristics, and targeting have been reviewed. We have also focused our discussion on radioresistance and adaptive responses of CSCs and their related extrinsic and intrinsic influential factors. In summary, we suggest CSCs as the prime therapeutic target for cancer treatment.